Search engines and global takedown orders: 'Google v Equustek' and the future of free speech online - Diab, Robert (Osgoode Hall law journal (1960), 2019)
The Supreme Court's decision in 'Google v Equustek' (2017) to uphold a global content takedown order remains controversial and consequential to wider debates about governing the internet. This commentary examines the Court's underlying assumption - a common view in takedown jurisprudence - that where a portal directs a critical mass of users to a harmful site, it facilitates harm and no longer engages in valuable speech. This ran contrary to the Court's more considered view of links in 'Crookes v Newton' (2011) as a form of mere reference and valuable per se for enabling the internet as a public forum. This commentary argues the Court should have applied its theory from 'Crookes' to search engine links as no different in principle from others, while conceding that, at scale, links that merely refer can facilitate harm. Drawing on the 'Copyright Act' and the Manila Principles on Intermediary Liability, the author proposes a test for takedown orders that strikes a better balance between free speech and private interests.